Biodegradation of mixtures of pesticides by bacteria and white rot fungi - Gouma, Sofia (Cranfield University, 2009)
The objective of this study was to examine the potential for degradation of mixtures of pesticides (chlorpyrifos, linuron, metribuzin) by a range of bacteria and fungi and to relate this capability to enzyme production and quantify the rates of degradation of the components of the mixture of xenobiotic compounds. Overall, although bacteria (19 Bacillus and 4 Pseudomonas species) exhibited tolerance to the individual and micture of pesticides actual degradation was not evident. Five species of white rot fungi were grown on minimal salts agar plates amended with 0, 10 and 30 mg L-1 of chlorpyrifos, linuron and metribuzin, individually and as a mixture with a total concentration 15 and 30 mg L-1. Four of these, T. versicolor, P. gigatea, P.coccineus and P.ostreatus, exhibited very good tolerance to the pesticides. They were also grown on a nutritionally poor soil extract agar amended with a mixture of the pesticides at different concentrations (0-70 mg L-1). Subsequently, the ability of T. versicolor, P. gigatea, P. coccineus to degrade lignin and production of laccase in the presence of mixture of the pesticides was examined as well as their capacity to degrade the pesticide mixture at different concentrations (0-50 mg L-1) in soil extract broth was quantified using HPLC. This showed that only T.versicolor had the ability to degrade linuron, after three weeks incubation although all tested species produced laccase. Subsequently, the temporal degradation rates of T.versicolor was examined in relation to temporal degradation of a mixture of the pesticides chlorpyrifos, linuron and metribuzin with total concentrations 0-50 mg L-1 and the temporal laccase production was quantified over a six week period in relation to ionic and non-ionic water potential stress (-2.8 MPa). These studies showed that the test isolate had the ability to produce very high levels of laccase at -2.8 MPa water potential adjusted non-ionically by using glycerol and quite lower levels in soil extract broth without stress while T.versicolor did not produce laccase at -2.8 MPa when the medium was modified ionically. Finally, T.versicolor was able to degrade the pesticide linuron in all tested water regimes, after five weeks incubation, regardless of the concentration of the mixture. In contrast, about 50% of the metribuzin was degraded, only at at -2.8 MPa water potential adjusted non-ionically with glycerol. Chlorpyrifos and its main metabolite TCP were not detected, possibly, due to a combination of hydrolysis, photolysis and volatilization degradation. The capacity of T.versicolor to degrade linuron in mixtures of pesticides and the production of high levels of laccase, in a nutritionally poor soil extract broth, even under water stress suggests potential application of this fungus in bioremediation.